KONSTRIBUSI MOTIVASI KERJA DOSEN TERHADAP EFEKTIVITAS PEMBELAJARAN DOSEN STKIP-PGRI SUMATERA BARAT - Edi Suarto (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2016)
This study aims to reveal konstribhusi Designing Capability Study and Work Motivation Against Efektigitas Learning Lecturer STKIP-PGRI Sumatera Barat. There are three hypotheses proposed in the research are The contribution of work motivation on the effectiveness of learning lecturer PGRI-STKIP Sumatera Barat,.This study uses a total sampling involving subjects were 71 lecturers. They are professors and lecturers PNSD Foundation. Data were collected through questionnaires and student grades. The data collected is then analyzed statistically using correlation and regression analysis. Results of the analysis showed that) Motivation has a significant contribution to the effectiveness of the learning faculty lecturer PGRI-STKIP Sumatera Barat amounted to 42.4%, Based on the above findings, it can be concluded that the ability to design learning and motivation are two factors which contribute to the effectiveness of learning lecturer STKIP PGRI West Sumatera